Highly diastereoselective entry into chiral spirooxindole-based 4-methyleneazetidines via formal [2+2] annulation reaction. Issue 77 (7th September 2016) - Rainoldi, G.; Faltracco, M.; Lo Presti, L.; Silvani, A.; Lesma, G.
Abstract : We describe here a diastereoselective, DABCO-catalyzed reaction of allenoates with chiral N-tert -butanesulfinyl ketimines derived from isatin. Abstract : A diastereoselective, DABCO-catalyzed reaction of isatin-derived ketimines with allenoates is described. Exploiting the stereodirecting effect of the bulky tert -butanesulfinyl chiral auxiliary, the method provides an efficient access to single diastereoisomers of unprecedented spirocyclic oxindoles, bearing a 4-methyleneazetidine ring at the spiro junction. The versatility of the method is fully demonstrated by further transformations including the conversion to relevant spirocyclic oxindolo-β-lactams.